The Gondwanan margin in West Antarctica: Insights from Late Triassic magmatism of the Antarctic Peninsula - Bastias Silva, Miguel Joaquin; Spikings, Richard Alan; Ulianov, Alexey; Riley, Teal; Burton-Johnson, Alex; Chiaradia, Massimo; Baumgartner, Lukas; Hervé, Francisco; Bouvier, Anne-Sophie (Gondwana Research, 2020)
Triassic orthogneisses of the Antarctic Peninsula provide evidence for the Palaeozoic and Mesozoic geological evolution of southern Gondwana within Pangaea. These rocks are sporadically exposed in southeastern Graham Land and northwestern Palmer Land, although reliable geochronological, geochemical and isotopic data are sparse. We combine new geochronological (LA-ICP-MS zircon UPb), geochemical, and zircon (Hf, O) and whole rock isotopic (Nd, Sr and Pb) data to constrain the age and Triassic – Palaeozoic tectonic setting of these rocks. Zircon cores record Palaeozoic arc magmatism between 253 ± 2 and 528 ± 6 Ma, which was mainly located to the west of the Eastern Palmer Land Shear Zone (Central Domain; Vaughan and Storey, 2000). The arc is considered to be an extension of contemporaneous Palaeozoic arcs that have been identified along the Pacific margin of South America and the Thurston Island Block. Regions to the east of the Palmer Land Shear Zone (Eastern Domain, Vaughan and Storey, 2000) were located distal from the Terra Australis Margin, and possibly resided within Sunsas-aged belts within Pangaea. Triassic continental arc, calc-alkaline magmatism during 223–203 Ma modified the crust of the Antarctic Peninsula on both sides of the Eastern Palmer Land Shear Zone. Magmatic sources included igneous and sedimentary crustal material, which formed by crustal reworking during Sunsas- and Braziliano-aged orogenesis, and Palaeozoic arc magmatism. Arc magmatism accompanied sinistral extension which brought both domains into the arc and resulted in steady oceanward migration of the Triassic arc during the Middle – Late Triassic. We propose that sinistral displacement occurred along the Eastern Palmer Land Shear Zone, and this structure was active as early as the Triassic. Finally, we conclude that both the Eastern and Central Domains are autochthonous to Gondwana.